2001
DOI: 10.1007/s007870170047
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial effusions in anorexia nervosa

Abstract: Anorexia nervosa is an eating disorder that may be accompanied by cardiac symptoms of varying severity. So far disturbances like arrhythmias, mitral valve prolapse and loss of cardial ventricle mass have been described. Other somatic complications consist of electrolyte and acid-base imbalances, which in turn influence cardiac function. Between 1990 and 1999 we observed ten case reports from inpatient anorexic female adolescents, who developed pericardial effusions in the course of their illness. The diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 0 publications
0
28
0
1
Order By: Relevance
“…In view of the literature to date, and the wide prevalence of reported AN-associated pericardial effusions, it is reasonable to consider preoperative echocardiography for patients in whom AN is suspected. *Not applicable or not available; **Referenced in Frolich et al [9]; ***While specific numbers are not listed here, this study reported clinically silent pericardial effusion that was inversely related to body mass index (BMI)…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In view of the literature to date, and the wide prevalence of reported AN-associated pericardial effusions, it is reasonable to consider preoperative echocardiography for patients in whom AN is suspected. *Not applicable or not available; **Referenced in Frolich et al [9]; ***While specific numbers are not listed here, this study reported clinically silent pericardial effusion that was inversely related to body mass index (BMI)…”
Section: Discussionmentioning
confidence: 88%
“…In these patients, most pericardial effusions resolved with nutritional support only. Conversely, one study of AN patients with pericardial effusions noted a correlation between normalization of body mass and resolution of effusions, yet in those cases there did not appear to be a significant protein deficiency [9].…”
Section: Discussionmentioning
confidence: 96%
“…3 Upon reviewing the adolescent eating disorder literature, the most common reported cardiovascular complications include electrocardiographic abnormalities such as sinus bradycardia, 1,[3][4][5] decreased voltage and prolonged QTc, 1,3-7 orthostatic hypotension, 8 increased vagal tone, 9,10 poor myocardial contractility, mitral valve prolapse (MVP), reduction in left ventricular wall thickness and mass, 3,9,11 and silent pericardial effusion. 11,12 Electrocardiographic abnormalities are present in most adolescents with AN. 3,4,6,7 Sinus bradycardia is reported to be present in 35-95% of adolescents with AN, 1,[3][4][5] and is believed to be due to the reported increased vagal tone 4,9,10 and decreased metabolic rate.…”
Section: Cardiovascular Complicationsmentioning
confidence: 99%
“…11,12 One study described 10 hospitalized adolescents with AN with pericardial effusions discovered on echocardiography. 12 No clinical signs or symptoms of heart failure were observed. In 8 of these adolescents, pericardial effusion remitted with weight rehabilitation.…”
Section: Debra K Katzman Md* Abstractmentioning
confidence: 99%
See 1 more Smart Citation